2008
DOI: 10.1007/s12291-008-0062-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic strategies for subclinical hypothyroidism

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 13 publications
3
23
0
Order By: Relevance
“…This finding is similar with the study done by Canaris et al [15], which mentioned that autoimmune thyroid diseases affect women 2 to 4 times more than men. In addition, Mohanty et al [16] showed that 45 of the 61 subclinical hypothyroid patients had elevated anti-TPO (73.78%), this finding also be in accord with our study. In agreement with our study Swain et al has also reported that most (95%) of the patients with autoimmune thyroid disease were women, mainly belonging to the age group of 30-50 years [2].…”
Section: Discussion:-supporting
confidence: 93%
“…This finding is similar with the study done by Canaris et al [15], which mentioned that autoimmune thyroid diseases affect women 2 to 4 times more than men. In addition, Mohanty et al [16] showed that 45 of the 61 subclinical hypothyroid patients had elevated anti-TPO (73.78%), this finding also be in accord with our study. In agreement with our study Swain et al has also reported that most (95%) of the patients with autoimmune thyroid disease were women, mainly belonging to the age group of 30-50 years [2].…”
Section: Discussion:-supporting
confidence: 93%
“…The worldwide prevalence of subclinical hypothyroidism ranges from 1 to 10% [18,19]. Since these patients develop overt hypothyroidism at the rate of 5% per year [19,20], it is important to identify these patients [21]. Typical biochemical picture suggestive of hypothyroidism was observed in 1.6% of samples.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Mohanty et al have showed that 45 of the 61 subclinical hypothyroid patients had elevated anti-TPO (73.78%), thereby suggesting an autoimmune aetiology for subclinical thyroid dysfunction and a higher risk of developing overt hypothyroidism in such patients. 4 Bjoro et al in a 20-year follow-up study, conducted among Norwegian inhabitants (94,009), have found that the positive anti-TPO levels correlated significantly with thyroid dysfunction and the prevalence of elevated TSH was nearly 10-fold higher in both females and males with positive anti-TPO when compared to anti-TPO-negative subjects. 6 The study by Silva et al, conducted in 89 Brazilian women, has noted elevated anti-TPO levels in around 90% of the patients with autoimmune thyroiditis.…”
Section: Discussionmentioning
confidence: 98%
“…3 Another Indian study by Mohanty et al, has reported that among the 38 frank hypothyroid patients, 76% had raised anti-TPO levels. 4 In a crosssectional study conducted in Rajasthan, the prevalence of hypothyroidism noted in the overall study population (n=300) was 9.33%. A significantly higher number of females (83.33%) than males (16.67%) were diagnosed with subclinical hypothyroidism and a total of 56 (18.66%) subjects tested positive for anti-TPO antibody.…”
Section: Introductionmentioning
confidence: 97%